Anotaciones al poema "Exhortación a una nave nueva al entrar en el agua", de Francisco de Quevedo - Moreno Castillo, Enrique (El Colegio de México, 2010)
This paper includes an analysis of Quevedo’s poem “Exhortación a una navenueva al entrar en el agua”. The antecedents of the theme in Horace andthe Greek Anthology are looked into; and the poem is compared to poems byseveral other 17th century Spanish authors. As well as that, plentiful noteselucidate any unclear expressions in the text of the poem, and highlight thedifferent themes and images placing them in their cultural context and literarytradition. The Príncipe de Esquilache’s song “A la nave” is printed inan appendix to show its similarities with Quevedo’s poem.